Pembelajaran Tematik Berbasis Kontekstual di Madrasah Ibtidaiyah Negeri 6 Kota Padang: Contextual Thematic Learning at State Elementary School 6, Padang City - Usdarisman, Usdarisman; Febianto, Debi; Basit, Abdul (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to (1) describe the contextual-based thematic learning plan that is implemented in MIN 6 Kota Padang, (2) describe contextual contextual teaching-learning in MIN 6 Kota Padang, (3)   describe contextual-based thematic learning evaluation in MIN 6 Kota Padang. Methods This study is a qualitative descriptive study that describes phenomena in the field without treatment. The object of this research is the students of grade V MIN 6 Kota Padang. Sources of data obtained from teachers and students of class V. In addition, learning tools are used when learning is implemented.   The primary data collection techniques are observation, documentation, and interviews as research support techniques. The results showed that contextual thematic learning planning at MIN 6 Kota Padang was good enough and run as it should be. Implementing contextually thematic learning at MIN 6 Kota Padang is still not by the planning. The practice of a contextual approach to thematic learning is still less than optimal because teachers are less well-understood when applying a contextual-based thematic approach. Finally, the thematic learning evaluation is implemented using the assessment standards. Learning evaluation includes assessing student learning outcomes, which include aspects of attitude, knowledge, and skills.